THE ANALYSIS OF STATE OF MOOD IN ATHLETES IRONMAN AND INCIDENCE OF THE RISK FACTORS FOR THE OVERTRAINING SYNDROME. (Fiep Bulletin - online, 2014)
The overtraining syndrome (SET) is considered a problem common among athletes due to fluctuations and imbalances between applicants of settings training, competitions and physical regeneration. The objective of the study was to examine the state of mood of athletes Ironman and the incidence of risk factors for the syndrome of excessive physical training. The sample was composed of 30 athletes amateurs belonging to a team of Florianopolis, regardless of sex and age, who completed the proof of Ironman in 2007. The instrument used for the evaluation of athletes was the classification of BRUMS, where used as reference the 50th percentile. The scale of mood was applied in seven different times chosen according to the period of training: at the peak of greater of training load; Before and after the training half Ironman; On the day preceding the proof sports; The day after the competition; five days and 12 days after the event. The results showed that most athletes submitted amendments above the 50th percentile (P50) in the following factors: A) In the peak of training: fatigue (P51 - P75), rabies (P52 - P91) and force (P52 - P70). B) Before training: fatigue (P51-P93) and force (P52 - P70). C) After training: fatigue (P51 - P96). D) The day before the race sports: force (P52 - P70) and voltage (P52 - P67). E) On the day after the competition: fatigue (P51 - P86) and force (P52 - P70). F) Five days and Twelve days: force (P52 - P70). The incidence of risk factors for the SET was 16.6%. It follows that the team presented swings of mood appropriate to the training load, showing good physical and psychological recovery before and after the competition.